REPRESENTAÇÕES SOCIAIS DOS MEMBROS DO CONSELHO MUNICIPAL DOS DIREITOS DA CRIANÇA E DO ADOLESCENTE DA CIDADE DE PONTA GROSSA-PR (CMDCA-PG) SOBRE OS ADOLESCENTES QUE COMETEM ATOS DE VIOLÊNCIA - Adur, Diego Sgarbossa (2014)
This research has as its object of study the Social Representations of the members of the Municipal Council for the Rights of the Child and Adolescent Ponta Grossa-PR (CMDCA-PG) about the teenager who commits acts of violence. This is a survey of qualitative nature in that the following methodological procedures were used: bibliographic research, documentary research, questionnaire with open and closed questions and semi structured interview using the technique of free association of ideas (BAUER; GASKELL, 2002, SPINK, 1999). The data were analyzed based on the Theory of Social Representations of Moscovici (1978) and interpreted based on the Methodology of Depth Hermeneutics (Thompson, 1995). The research was restricted to the CMDCA-PG and the subjects of this research were members of this board who spontaneously expressed interest in participating in the study. From sixteen members, nine have offered to participate. The data analysis originated five categories: Public Policies; Violation of Rights; Punishment; Family; and Teenager that Commits Acts of Violence. The results showed that the Social Representation of members of CMDCA-PG about the teenager who commits acts of violence brings some evidences that bring back the initial stages of the preparation of policies and laws aimed at this population. Traits such as lack of social belonging, fragile emotional bonds, vulnerable family structure, lack of public policies, drugs and lack of life project, also were evidenced in identifying of teenager who commits acts of violence by the counselors.